2021
DOI: 10.3390/atmos12121632
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Hall-MHD Turbulence at Sub-Ion Scales: Spectral Transfer Analysis

Abstract: We present results of a multiscale study of Hall-magnetohydrodynamic (MHD) turbulence, carried out on a dataset of compressible nonlinear 2D Hall-MHD numerical simulations of decaying Alfvénic turbulence. For the first time, we identify two distinct regimes of fully developed turbulence. In the first one, the power spectrum of the turbulent magnetic fluctuations at sub-ion scales exhibits a power law with a slope of ∼−2.9, typically observed both in solar wind and in magnetosheath turbulence. The second regime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…We plan to continue this work using the spectral transfer analysis that allows a clearer connection between the different energy-transfer channels and the power spectra (see Papini et al 2021). We also plan to extend this analysis to a threedimensional geometry (see Verdini et al 2015;Franci et al 2018) to investigate the anisotropy of the energy cascade and dissipation including the pressure-strain effect.…”
Section: Discussionmentioning
confidence: 99%
“…We plan to continue this work using the spectral transfer analysis that allows a clearer connection between the different energy-transfer channels and the power spectra (see Papini et al 2021). We also plan to extend this analysis to a threedimensional geometry (see Verdini et al 2015;Franci et al 2018) to investigate the anisotropy of the energy cascade and dissipation including the pressure-strain effect.…”
Section: Discussionmentioning
confidence: 99%
“…Electron and ion energisations are expected to work at very different scales (Franci et al 2022), but comparable scales are observed in some full-particle simulations (Yang et al 2022). It is also unclear what the role of the turbulence anisotropy is (most of the present simulations are two-dimensional) and how it compares to other processes such as Hall coupling (Papini et al 2019(Papini et al , 2021. In this paper we extended the two-dimensional work of Hellinger et al (2022), we analysed a three-dimensional hybrid simulation of decaying plasma turbulence using the KHM equation, and we studied the anisotropy of different turbulent processes.…”
Section: Introductionmentioning
confidence: 70%
“…We plan to continue this work using the spectral transfer analysis that allows a clearer connection between the different energy-transfer channels and the power spectra (cf., Papini et al 2021). We also plan to extend this analysis to a three-dimensional geometry (cf., Verdini et al 2015;Franci et al 2018) to investigate anisotropy of the energy cascade and dissipation including the pressure-strain effect.…”
Section: Discussionmentioning
confidence: 99%